(untitled) (Research, Society and Development, 2021)
The 1988 Constitution states that education is a right of all and a duty of the State and the family, being promoted and encouraged with the collaboration of society, aiming at the full development of the person, their preparation for the exercise of citizenship and their qualification for the Work. In this sense, this article intends to concisely analyze the forms of action of the Public Ministry in promoting the right to education of children and adolescents in the national legal system. Therefore, a doctrinal review was used, along with a qualitative bibliographic analysis of articles, theses and dissertations, in addition to institutional documents. At first, it is clear that Parquet is the legitimate institution to defend unavailable collective, diffuse and individual interests and it is precisely at this point that the basic right to education of children and adolescents is highlighted, due to the fact that its homogeneity and trans-individuality authorize the ministerial body to act in defense of such right. Furthermore, throughout the work, the main characteristics of the principle of full protection of children and adolescents were analyzed, always in light of the Constitution and Law 8069/90, as well as explaining its relevance in the Brazilian legal system. Lastly, the legitimacy of the Public Ministry in proposing measures to ensure the right to education for children and adolescents is highlighted.